Between Performance and Action: Igralke - Petranović, Martina (Poznańskie Studia Slawistyczne, 2025)
The paper titled Between Performance and Action: Igralke examines the Rijeka theatre Collective Igralke and their productions Bakice / Grannies (2020), Crna vuna / Black Wool (2022) and Cure / Girls (2023). It focuses on the complex relationships and (overstepped) boundaries between the art and social engagement, social inclusion and social discrimination in theatre with regard to both form and content, interplay of personal and social narratives concerning several involved minority groups such as elderly women or homeless people, inclination towards democratic procedures in creative processes and production itself, as well as strategies, approaches and outcomes related to applied (community related agendas, community participation, community performance) and documentary theatre (the usage of documentary materials, capturing the “real”, probing the nature of true and authentic).